Improved National Results With Simultaneous Liver‐Kidney Transplantation Using Donation After Circulatory Death Donors. Issue 3 (3rd February 2020) - Croome, Kristopher P.; Mao, Shennen; Yang, Liu; Pungpapong, Surakit; Wadei, Hani M.; Taner, C. Burcin
Abstract : Previous large registry studies have demonstrated inferior outcomes for simultaneous liver‐kidney transplantation (SLKT) recipients of grafts from donation after circulatory death (DCD) donors compared with those from donation after brain death (DBD) donors in the era from 2000 to 2010. Given the improving national results in liver transplantation alone using grafts from DCD donors, the present study aimed to investigate if results with DCD‐SLKT have improved in the modern era. Patients undergoing SLKT between 2000 and 2018 were obtained from the United Network for Organ Sharing Standard Analysis and Research file and divided into 2 eras based on the date of SLKT: era 1 (2000‐2010) and era 2 (2011‐2018). Improvement in DCD‐SLKT patient, liver graft, and kidney graft survival rates was seen between era 1 and era 2 ( P  < 0.001). Concurrently, there was a decrease in the proportion of critically ill ( P  = 0.02) and retransplant ( P  = 0.006) candidates undergoing DCD‐SLKT. When DCD‐SLKT in era 2 was compared with a propensity‐matched cohort of DBD‐SLKT in era 2, no differences in patient ( P  = 0.99), liver graft ( P  = 0.19), or kidney graft ( P  = 0.90) survival were observed. In addition, both bilirubin (0.5 versus 0.5 mg/dL; P  = 0.86) and creatinine (1.2 versus 1.2 mg/dL; P  = 0.68) at last follow‐up were not different between the DCD‐SLKT and DBD‐SLKT patients in era 2. In conclusion, in the most recent era, patients undergoing DCD‐SLKT were able to achieve similar outcomes compared with matched patients undergoing DBD‐SLKT. DCD‐SLKT represents a viable option for appropriately selected recipients.